2016
DOI: 10.3390/jfmk1010039
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Displaced Supracondylar Pediatric Humerus Fractures: Comparison of Two Pinning Techniques

Abstract: The aim of this study is to report the results of the treatment of displaced supracondylar humerus fractures comparing two different techniques, crossed and lateral pins. We retrospectively reviewed 35 children hospitalized between May 2005 and December 2012. Patients were treated with two different pin configurations, crossed (Group 1) and lateral (Group 2). After surgery, clinical and radiographic evaluation was performed. Postoperatively, the clinical assessment showed recovery of joint function of the elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…In a study by Pavone et al similar outcomes were reported with either by crossed or lateral pinning of supracondylar humerus fractures in children [33]. Gopinathan et al reported that Baumann’s angle was 76.05° when a configuration of three parallel K-wires was used and 73.9° when a divergent K-wire configuration was used [34].…”
Section: Discussionmentioning
confidence: 70%
“…In a study by Pavone et al similar outcomes were reported with either by crossed or lateral pinning of supracondylar humerus fractures in children [33]. Gopinathan et al reported that Baumann’s angle was 76.05° when a configuration of three parallel K-wires was used and 73.9° when a divergent K-wire configuration was used [34].…”
Section: Discussionmentioning
confidence: 70%
“…This confirms crossed wire fixation to be equally accurate and a safe treatment option for Gartland type II and III fractures. 3,[27][28][29][30][31] We excluded Gartland type I since it is usually treated conservatively. 25 Our study was limited owing to the fact that it was conducted in a single tertiary care setup, with a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strengthening exercises do not begin until at least 2 months after surgery and heavy activity after about 6 months. It is known that surgery is not without complications, which are mainly two types: ectopic that may form between the radius and ulna proximally with pain and reduced joint mobility, and load nerve deficits in the lateral cutaneous nerve, the posterior interosseous nerve or radial nerve 19 tend the elbow while bending must be passive. Subsequently, the patient is encouraged to actively flex and extend the elbow in addition to active forearm rotation.…”
Section: Discussionmentioning
confidence: 99%